Because your vampire said so - Bardsley, Michele (A Signet Eclipse book, 2008)
Single mom and hair salon owner Patsy Donahue, still getting acclimated to her new vampire lifestyle, tries to rein in her wild teenage son while trying to deny her attraction to a rogue shape-shifter.